Analisis Kemampuan Pemecahan Masalah Ekonomi Manajerial Mengacu Pada Teori Polya Ditinjau dari Kemampuan Matematis - Setyowati, Suci Yongki; Nikmah, Nafidatun (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2025)
This research aims to determine the problem-solving ability of students in managerial economics courses reviewed from mathematical abilities. Mathematical abilities are closely related to the managerial economics aspect. In the scope of managerial economics, it broadly covers economic problems that are closely related to the calculation process. This study was conducted at Sunan Drajat University, Lamongan. The population used in this study were 4th semester students of the Faculty of Islamic Economics and Business who took the managerial economics course. The research instrument was in the form of high school level mathematics questions used to determine the level of students' mathematical abilities. Another instrument used by researchers to determine the problem-solving ability of students in the Islamic Economics and Business study program at UNSUDA Lamongan was 2 questions related to optimization in managerial economics. This study is a descriptive study that provides an overview of the process of solving managerial economic problems that pay attention to aspects of mathematical abilities. The results of the study showed that students with high mathematical abilities had problem-solving abilities in the managerial economics course in the very good category. Students with moderate mathematical abilities had problem-solving abilities in the managerial economics course in the good category. Meanwhile, students with low mathematical abilities have problem-solving abilities in managerial economics courses in the less category.